EMPLOYEE JOB SATISFACTION WITHIN THE FRAMEWORK OF CONTEMPORARY MANAGEMENT - Pechová, Jana; Matoušková, Ingrid; Velinov, Emil (Veredas do Direito, 2025)
Job satisfaction represents a multidimensional construct with a critical impact on employee performance, organizational stability, and the long-term sustainability of business processes. In the context of increasing demands on strategic human resource management and the effectiveness of implemented measures, the systematic diagnosis of job satisfaction is gaining importance as a key tool of evidence-based management. The present study is grounded in the theoretical framework of behavioral motivational approaches and Kirkpatrick’s four-level model of training evaluation, which allows for the connection of perceived changes in the work environment with specific organizational interventions. Based on an analysis of current practices and identified needs in the field, a diagnostic tool has been designed in the form of a standardized form intended for managers, HR specialists, and internal evaluators. This tool is being tested within an organizational setting through a quantitative survey aimed at validating its sensitivity to changes in key dimensions of employee satisfaction. The aim of this paper is to provide a practically applicable and methodologically robust instrument that enables the systematic measurement of intervention effectiveness, supports data-driven decision-making, and contributes to the refinement of personnel policy in line with the principles of sustainable and integrated leadership.